Threats to sustainability in face of post-pandemic scenarios and the war in Ukraine - da Costa, João Pinto (2023)
As the World slowly emerged from the then-ongoing pandemic, War broke out in Europe with the invasion of Ukraine by Russia. The enduring military conflict in Ukraine has had sweeping consequences at the human, social, economic, and environmental levels, not only for the nations involved but across Europe and globally. Damaged infrastructures, severe disruption of economic activity, and forced migration have led to negative impacts on sustainability. The COVID-19 pandemic has added another layer of complexity to this already challenging situation, as the virus has further disrupted economic activity and strained healthcare systems. Herein, we examine how the intersection of war and COVID-19 affect the United Nations' 2030 Agenda for Sustainable Development. How these intersecting challenges have impacted efforts to build a more sustainable future, and how these impacts have a global reach are also assessed. The broader implications of this case for understanding the linkages between conflict, pandemics, and sustainability more generally are also considered, relating these with the United Nations' Sustainable Development Goals (SDG) Agenda for 2030.